DEVELOPMENT OF URBAN TOURISM; EMPHASIZING IMPACT OF CLIMATIC FACTORS: A CASE STUDYOF FARSAN COUNTY (Singaporean Journal of Business Economics and Management, 2015)
Today, tourism industry can be considered as one of the biggest existing industries and one of the most important branches of industry and trade around the world and is in top of job creative industries. According to importance of tourism industry, in addition to cultural, social and political factors, environmental factors play also key role in development of tourism and attraction of tourist. The main aim of the present study is development of urban tourism emphasizing impact of climatic factors and Farsan County has been investigated as case study. Applied method in this study has been descriptive-analytical method. Statistical population of the study includes experts of Farsan in field of tourism and climatology, in which 50 persons have been selected as sample using snowball sampling method. According to obtained results from regression analysis, climatic factors can affect development of tourism to 31%; change in seasons and weather to 20%; codifying effective strategies to 35% and attracting investors can affect it to 14%. Therefore, through focusing on these factors, one can improve tourism development todesirable level of development plans.